Falas ecolálicas: uma discussão sobre a multiplicidade de seus efeitos - Santos, Iara Maria Ferreira dos (2015)
The so-called echolalia was the subject discussed in this paper. I was interrogated due to the fact that every child starts speaking by incorporating the speech of others, but there are those, especially the ones within the psychopathology group, who are stuck in this position and, practically, only repeat their interlocutor s words. Thus, I found it intriguing and stimulating that the same event the repetition of their interlocutor s words would be children s gateway to language but also being present in complex clinical cases. So as to prompt reflection upon this theme I visited the interactionism, as proposed by De Lemos, who took the repetition of one s speech as a privileged space of theorization (De Lemos, 1982, 1992, 2002 amongst others). In clinical literature, only a few papers have explored the articulation of this phenomenon with the subjective structuring, to this end, I chose for interlocution the researchers from Grupo de Pesquisa Aquisição, Patologias e Clínica de Linguagem who had already approached the subject: Lier-DeVitto (1998, 2006 amongst others), Arantes (2001a, 2011) and Oliveira (2001). In regards to methodology, to illustrate the discussion, I based myself in data by authors that dealt with the speech of children who insisted in blocks (Arantes, 2011; Oliveira, 2011). Overall, this paper explores the effects of repetition regarding the subjective structuring. Thus, taking the individual for their unconscious marks, I found it necessary to visit the concept of repetition and holophrase as they appear in psychoanalyses (Freud, 1914, 1920; Lacan, 2008), aiming to distinguish repetition as incorporation of the interlocutor s speech in the cases when they have success from the ones when the children fail. From psychoanalysis, I could gather that in a trajectory without accidents, repetition is a consequence of the operations of alienation and separation. When problems arise in the period of the subjective structuring, the scenario is totally different. In the case of the children mentioned in this dissertation, I concluded that we cannot speak of repetition, since the alienation and separation operations are not concluded